Interpretation of democracy, pluralism and tolerance among the young activists of Muhammadiyah and Nahdlatul Ulama - Ali Maksum; Priyono Tri Febrianto; Esa Nur Wahyuni (Masyarakat, Kebudayaan dan Politik, 2019)
Anarchism and other forms of violence committed by religious groups and mass organizations are still very common in Indonesia. There have been violations of human rights, religious freedom and civil liberties, which are essential pillars of democracy. Indonesia, as a country that adheres to religious freedom regards all forms of intolerance as violations of democracy. This study described and explored the views of young cadres of Muhammadiyah and Nahdlatul Ulama (NU) in Malang, East Java, about democracy, pluralism and tolerance. This research intended to unravel some of the issues of how young generations of Muhammadiyah and NU understand democracy, pluralism and tolerance and if their views are associated with their social construction. This study employed qualitative methods using interviews and direct observations to collect the data. The results of this study showed there were differences in the patterns between the younger generation and the older generation of Muhammadiyah. The members of Muhammadiyah recognized that the young cadres of Muhammadiyah tended to act more violently towards intolerant mass organizations compared to their senior (old cadre) generation. The senior cadres, such as the Muhammadiyah Youth, were more likely to be calm when responding to the presence of radical organizations. The senior cadres of Muhammadiyah tended to be open-minded with the community organizations that are perceived by the public to be a radical mass organization, which is fundamental in addressing the presence of radical organizations. This view indicated by the absence sense of precariousness or a situation that is considered to be very threatening to religious and national life while still in the corridor of diversity. On the other hand, the younger generation of Nahdlatul Ulama showed a different pattern, revealing that their seniors tended to be harsher in responding to radical organizations and supporting mass organizations.